2023
DOI: 10.1038/s41556-022-01053-0
|View full text |Cite
|
Sign up to set email alerts
|

Stromal niche inflammation mediated by IL-1 signalling is a targetable driver of haematopoietic ageing

Abstract: Hematopoietic aging is marked by a loss of regenerative capacity and skewed differentiation from hematopoietic stem cells (HSC) leading to impaired blood production. Signals from the bone marrow (BM) niche tailor blood production, but the contribution of the old niche to hematopoietic aging remains unclear. Here, we characterize the in ammatory milieu that drives both niche and hematopoietic remodeling. We nd decreased numbers and functionality of osteoprogenitors (OPr) and expansion of pro-in ammatory perisin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 72 publications
3
46
0
Order By: Relevance
“…9294 Furthermore, an inflammatory bone marrow niche in aged mice, including IL-1β produced by a damaged endosteum, leads to increased myelopoiesis and impaired hematopoietic recovery. 95 In agreement with the second hypothesis are data from zebrafish where subclonal CH mutations lead to expression of pro-inflammatory genes in mature mutant myeloid cells but anti-inflammatory genes in mutant HSPCs, providing them with a relative fitness advantage. 96 In mice when TET2 MUT subclones are exposed to IL-1, they functionally outcompete WT HSCs.…”
Section: Discussionsupporting
confidence: 57%
“…9294 Furthermore, an inflammatory bone marrow niche in aged mice, including IL-1β produced by a damaged endosteum, leads to increased myelopoiesis and impaired hematopoietic recovery. 95 In agreement with the second hypothesis are data from zebrafish where subclonal CH mutations lead to expression of pro-inflammatory genes in mature mutant myeloid cells but anti-inflammatory genes in mutant HSPCs, providing them with a relative fitness advantage. 96 In mice when TET2 MUT subclones are exposed to IL-1, they functionally outcompete WT HSCs.…”
Section: Discussionsupporting
confidence: 57%
“…72 Interestingly, the effects of IL-1-driven proinflammatory aging effects in the niche were reversible upon targeting of IL-1 signaling. 71,72…”
Section: Examination Of Cell-intrinsic Changes Upon Agingmentioning
confidence: 99%
“…72 Interestingly, the effects of IL-1-driven proinflammatory aging effects in the niche were reversible upon targeting of IL-1 signaling. 71,72 A recent study demonstrated impaired mitochondrial function in aged HSPCs when stressed with LPSs. 73 HSPC malfunction during stress was supported by the accumulation of senescent, p16 INK4Apositive MSCs that naturally occur with aging in the bone marrow.…”
Section: Examination Of Aging-related Changes In the Bone Marrow Micr...mentioning
confidence: 99%
See 2 more Smart Citations